PENERAPAN MODEL PEMBELAJARAN AWARENESS TRAINING UNTUK MENINGKATKAN PERCAYA DIRI DAN PRESTASI BELAJAR SISWA (Studi Pada Mata Pelajaran Seni Budaya Siswa kelas IX di SMP Negeri 1 Lahat) - Eka Fatriyarni; Johanes Sapri (UNIB Press, 2020)
The purpose of this study is to describe the application of the Awareness Training learning model to increase student confidence in arts and culture subjects, describe the application of the Awareness Training learning model to improve student achievement and to describe the effectiveness of the application of the Awareness Training learning model in improving learning achievement in IX grade students of SMP Negeri 1 Lahat. This study uses Classroom Action Research (CAR) and to determine the effectiveness of the Awareness Training learning model is carried out using the Quasi Experiment research model. Data collection is done by observation and tests. The subjects of Classroom Action Research are students of class IX 5, the determination of the experimental class and the control class by random / random selection, students of class IX 3 as the experimental class, and students of class IX 1 as the control class. Based on research carried out for three cycles the results of the analysis showed a significant increase. It can be concluded that the application of the awareness training model can increase self-confidence, the application of the awareness model can improve student learning achievement, the application of the awareness training learning model can effectively increase the confidence and student achievement in SMP Negeri 1 Lahat.